Acute Renal Failure in Newborns with Birth Asphyxia - KC, Rajesh; Kanodia, Piush; Sah, Shyam Nandan; Adhikari, Sumit (Journal of Nepalgunj Medical College, 2022)
Introduction: Perinatal asphyxia is one of the common causes of neonatal morbidity and mortality. It can affect almost all the body organs and most frequently affected organs are kidneys. Acute Renal Failure is the commonest renal complication, manifested by changes in urine output and blood chemistries. Aims: To evaluate the renal function in asphyxiated newborns. Methods: This cross-sectional study was conducted, from August 2021 to February 2022, on 95 term neonates admitted in Neonatal Intensive Care Unit of Nepalgunj Medical College, Kohalpur for birth asphyxia as per World Health Organization definition. All neonates with Hypoxic Ischemic Encephalopathy were staged by Sarnat and Sarnat staging. After 48 hours of life, blood sample was sent for investigations. Urine output was monitored and neonates were managed according to the hospital protocol. Results: Male to female ratio was M:F 1.90:1. Percentage of acute renal failure was higher in babies with higher Hypoxic Ischemic Encephalopathy grades. It was seen in 12% in Grade I, 82% in Grade II and 100% in Grade III. Renal failure had significant association with Hypoxic Ischemic Encephalopathy staging(p<0.05).The means of serum creatinine significantly increased with the increase in Hypoxic Ischemic Encephalopathy grades (p<0.05). Mean serum creatinine among Grade I, Grade II and Grade III newborns were 0.9±0.44, 2.2±.93and 2.9±0.38 mg/dl respectively. Mean urinary output significantly decreased as the grades of Hypoxic Ischemic Encephalopathy increased (p<0.05) with mean urine output 1.5±0.38, 1.3±0.53and 1.1±0.39 ml/kg/hour respectively in Grade I, Grade II and Grade III. Conclusion: Neonates with higher grades of Hypoxic Ischemic Encephalopathy had higher values of serum creatinine. Urine output decreased as the grading of asphyxia increased